Capacity Development and Multi-Tiered Systems of Support: Guiding Principles*. Issue 2 (16th November 2016) - Sugai, George; Simonsen, Brandi; Freeman, Jennifer; La Salle, Tamika
Abstract : Implementation of multi-tiered systems of support is occurring within and across a number of countries with an increased recent focus on the development of local system capacity to maintain high levels of practice implementation fidelity. The purpose of this paper is to describe the importance of local capacity development in the high fidelity and sustained implementation of empirically supported practices within a multi-tiered system of support. After we describe the rationale for, and descriptions of, capacity development and multi-tiered systems of support, we (a) present a framework for the development of implementation capacity, (b) emphasise guiding concepts and principles, and (c) use positive behavioural interventions and supports as an example of a capacity development framework. We conclude with implications and recommendations.